2019
DOI: 10.1109/tnsre.2019.2921710
|View full text |Cite
|
Sign up to set email alerts
|

The Body’s Compensatory Responses to Unpredictable Trip and Slip Perturbations Induced by a Programmable Split-Belt Treadmill

Abstract: This paper investigates the influence of two types of gait perturbation (i.e., trip and slip) induced by a programmable split-belt treadmill on the body's compensatory responses. Our fall-inducing technology equipped with a commercially available programmable split-belt treadmill provides unpredictable trip and slip perturbations during walking. Two force plates beneath the split-belt treadmill and a motion capture system quantify the body's kinetic and kinematic behaviors, and a wireless surface electromyogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…The equipment shown in Fig 1 has been used recently [25,26]. The fall-inducing platform including a programmable split-belt treadmill equipped with two force plates located beneath each belt (Bertec, Columbus, OH, USA) and controlled by our custom software [18,19,27] was used to induce slips by accelerating the left belt in the anterior direction (i.e., the perturbation occurred at the foot level).…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…The equipment shown in Fig 1 has been used recently [25,26]. The fall-inducing platform including a programmable split-belt treadmill equipped with two force plates located beneath each belt (Bertec, Columbus, OH, USA) and controlled by our custom software [18,19,27] was used to induce slips by accelerating the left belt in the anterior direction (i.e., the perturbation occurred at the foot level).…”
Section: Instrumentationmentioning
confidence: 99%
“…All trials ended 10 steps after the perturbation to account for the number of steps required to return to normal walking [19,30] and the latency of the hemodynamic response subsequent to the perturbation (approximately 4 to 7 s) [34]. Normal walking resumed within 3 to 4 steps after a slip, corresponding to 4.2 ± 0.9 s. In all trials, during standing and walking, participants were required to fix their gaze on an "X" placed approximately 4.5 m ahead at eye level to stabilize their posture and minimize head movements and side-to-side walking variations [25,26]. Consecutive trials were separated by a rest period (20 s) to allow brief relaxation of the torso and upper and lower extremities.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of our previous studies (Lee et al, 2017a(Lee et al, ,b, 2019(Lee et al, , 2020Yoo et al, 2019) and our pilot study, the power analysis indicated a minimum of 20 participants, with an effect size (f ) = 0.67 (large effect size) (Cohen, 1992) The Nexus 1.8 software synchronized with the EMG system and the custom software sampled the EMG signals at 2000 Hz and the marker positions and the ground reaction forces (GRFs) at 100 Hz, respectively [see the detailed algorithm information in (Lee et al, 2017a); see the custom software information in (Lee et al, 2017a(Lee et al, , 2019Yoo et al, 2019)]. The custom software generated split-belt treadmill perturbations (at the foot level) by stopping the treadmill's left belt within 100 ms at a rate of 10 m/s 2 at 10% of the gait cycle (approximately the loading phase) determined by GRFs (Lee et al, 2017a(Lee et al, , 2020Yoo et al, 2019).…”
Section: Methods Participantsmentioning
confidence: 99%
“…The Plug-in-Gait model is a standard and reliable tool in biomechanics research for analyzing joint moments, especially for the sagittal plane (Kadaba et al, 1989). Previous studies found that the whole-body movement predominated in the sagittal plane after trip perturbations (Lee et al, 2017a(Lee et al, , 2019. The low-pass filter was applied to the GRFs by a secondorder Butterworth filter with a cut-off frequency of 10 Hz using MATLAB (The MathWorks, Natick, MA, USA) (Lee et al, 2019).…”
Section: Data Processingmentioning
confidence: 99%